Pelatihan Teknik Dasar Pembuatan Desain Presentasi Menggunakan Microsoft PowerPoint - Winarti, Dwi; Hoesain M, Ismail (Universitas Mataram, 2025)
Abstract: The imperative for higher digital literacy among lecturers and students stems from science and technological progress, especially regarding the use of Microsoft PowerPoint (PPT) as a presentation aids. The main challenge faced is the low knowledge of students in compiling presentation material points, PPT features, and a lack of skills in PPT practice, which often results in monotonous and less informative. This community service program aims to improve students’ basic techniques knowledge and skills in creating presentation designs using PPT. This activity applies quantitative methods through an educational and training approach, covering materials such as field data visualization, PPT features, and PPT practice. This program was carried out in collaboration with The D3 Mining Engineering Student Association, Universitas Muhammadiyah Mataram as a partner, involving 16 participants. Evaluation was carried out through pre-test and post-test to measure changes in participants’ knowledge and skills using a Likert scale. The highest increase is about PPT features which is 42,50% from 36,25% to 78,75%, followed by PPT practice by 40,62% from 39,39% to 80,00%, and the lowest is field data visualization which is 37,50% from 35,00% to 72,50%. The average knowledge and skill enhancement among students reached 40,62%. Four of the students who had the highest knowledge and skills, reached 93,33% after training from 40,00% - 53,33% previously. Based on the evaluation, this program is considered successful, as evidenced by the increase in students’ knowledge and skills of all training materials presented. Overall, implementation of the activities went smoothly. Keywords: Digital Literacy; Students; Mining; Presentation; Likert Scale